168k views
2 votes
Enter the value of n so that the expression (ny+25.7)+(−45.2y+13.9) is equivalent to (−33.7y+39.6). n=

Help and I will give you Brainllest.

1 Answer

3 votes

Answer:


n=11.5

Explanation:

Given:

The two expressions are:


(ny+25.7)+(-45.2y+13.9)=(n-45.2)y+39.6


-33.7y+39.6

If the above 2 expressions are equivalent, then the coefficients of
y should be equal for both the expressions.

The coefficient of
y in the first expression is:


(n-45.2).

The coefficient of
y in the second expression is:


-33.7.

Therefore,


n-45.2=-33.7\\n=-33.7+45.2=11.5

User Tim Windsor Brown
by
5.1k points